2017
DOI: 10.3171/2016.7.spine16448
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obesity on complications and outcomes: a comparison of fusion and nonfusion lumbar spine surgery

Abstract: OBJECTIVE Prior studies have shown obesity to be associated with higher complication rates but equivalent clinical outcomes following lumbar spine surgery. These findings have been reproducible across lumbar spine surgery in general and for lumbar fusion specifically. Nevertheless, surgeons seem inclined to limit the extent of surgery, perhaps opting for decompression alone rather than decompression plus fusion, in obese patients. The purpose of this study was to asc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 30 publications
(42 reference statements)
2
42
1
Order By: Relevance
“…Previous studies showed that obese patients have a higher incidence of complications. [29][30][31] However, the present study showed a different result. The patient population in our study was over 70 years of age and the average BMI was 25.2±3.5, which did not reach the obesity range.…”
Section: Discussioncontrasting
confidence: 83%
“…Previous studies showed that obese patients have a higher incidence of complications. [29][30][31] However, the present study showed a different result. The patient population in our study was over 70 years of age and the average BMI was 25.2±3.5, which did not reach the obesity range.…”
Section: Discussioncontrasting
confidence: 83%
“…Specific patient characteristics such as diabetes, gender, obesity, smoking, and comorbidities, or severity of stenosis and number of decompressed levels have been shown not to be associated with higher reoperation rates. 10,17,20,21 However, one study found patients covered by workers' compensation to be at a substantially higher risk of reoperation. 11 Since the mean age of patients in our study was above retirement age that would not have had a significant impact on our results.…”
Section: Risk Factors For Reoperation Following Decompressionmentioning
confidence: 99%
“…3,[12][13][14][15][16][17] Obese patients can benefit significantly from spinal surgery, especially using a minimally invasive technique. 6,18 These techniques provide a beneficial alternative for obese patients, minimizing postoperative complications. 19 Three studies have reported the results from endoscopic transforaminal lumbar discectomy in obese patients.…”
Section: Discussionmentioning
confidence: 99%